CREATING AND MARKETING AN IDEAL INVESTMENT ENVIRONMENT - J. Jegathesan (Asian Academy of Management Journal, 1996)
The focus of this paper is on attracting the "export-oriented investor". An investor has the free choice of various locations in any region, or even the world, for the establishment of his project. Many developing countries and in fact most developed countries are "bending backwards" to either attract or retain the manufacturer who has an export-oriented project.